ANALISIS PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATERI BANGUN DATAR KELAS IV SDN PLAMONGANSARI 02 - Fatichasari, Rizki Azzahra; Agustini, Ferina; Listyarini, Ikha (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This research aims to determine the use of the problem based learning (PBL) learning model implemented in implementing mathematics learning in class IV at SDN Pramongansari 02. This activity uses a qualitative descriptive research method. Data collection through observation and recording. All 22 fourth grade students at SDN Plamongansari 02 participated in this research as participants. Based on research activities carried out, the problem-based learning model used in class IV mathematics learning at SDN Pramongansari 02 Semarang has been successfully implemented and includes five phases in the PBL cycle. Student responses to the Problem Based Learning (PBL) learning model are very positive because students are able to learn with the PBL model. Based on the evaluation of student participation in implementing learning steps and problem solving, the implementation of the problem-based learning model at SDN Pramongansari 02 for class IV students was considered successful.